Transcriptomic Analysis of Intestinal Tissues from Two 90-Day Feeding Studies in Rats Using Genetically Modified MON810 Maize Varieties - Sharbati, Jutta; Bohmer, Marc; Bohmer, Nils; Keller, Andreas; Backes, Christina; Franke, Andre; Steinberg, Pablo; Zeljenková, Dagmar; Einspanier, Ralf (Frontiers in Genetics, 2017)
Background: Global as well as specific expression profiles of selected rat tissues were characterized to assess the safety of genetically modified (GM) maize MON810 containing the insecticidal protein Cry1Ab. Gene expression was evaluated by use of Next Generation Sequencing (NGS) as well as RT-qPCR within rat intestinal tissues based on mandatory 90-day rodent feeding studies. In parallel to two 90-day feeding studies, the transcriptional response of rat tissues was assessed as another endpoint to enhance the mechanistic interpretation of GM feeding studies and/or to facilitate the generation of a targeted hypothesis. Rats received diets containing 33% GM maize (MON810) or near-isogenic control maize. As a site of massive exposure to ingested feed the transcriptomic response of ileal and colonic tissue was profiled via RT-qPCR arrays targeting apoptosis, DNA-damage/repair, unfolded protein response. For global RNA profiling of rat ileal tissue, we applied NGS. Results: No biological response to the GM-diet was observed in male and in female rat tissues. Transcriptome wide analysis of gene expression by RNA-seq confirmed these findings. Nevertheless, gene ontology analysis clearly associated a set of distinctly regulated transcripts with circadian rhythms. We confirmed differential expression of circadian clock genes using RT-qPCR and immunoassays for selected factors, thereby indicating physiological effects caused by the time point of sampling. Conclusion: Prediction of potential unintended effects of GM-food/feed by transcriptome based profiling of intestinal tissue presents a novel approach to complement classical toxicological testing procedures. Including the detection of alterations in signalling pathways in toxicity testing procedures may enhance the confidence in outcomes of toxicological trials. In this study, no significant GM-related changes in intestinal expression profiles were found in rats fed GM-maize MON810. Relevant alterations of selected cellular pathways (apoptosis, DNA damage and repair, unfolded protein response) pointing toward intestinal toxicity of the diets were not observed. Transcriptomic profiles did not reveal perturbations of pathways associated with toxicity, underlining the study results revealed by classical OECD endpoints.